Glycemic Variability Promotes Both Local Invasion and Metastatic Colonization by Pancreatic Ductal AdenocarcinomaSummary - Ziying Jian (Cellular and Molecular Gastroenterology and Hepatology, 2018)
Background & Aims: Although nearly half of pancreatic ductal adenocarcinoma (PDAC) patients have diabetes mellitus with episodes of hyperglycemia, its tumor microenvironment is hypoglycemic. Thus, it is crucial for PDAC cells to develop adaptive mechanisms dealing with oscillating glucose levels. So far, the biological impact of such glycemic variability on PDAC biology remains unknown. Methods: Murine PDAC cells were cultured in low- and high-glucose medium to investigate the molecular, biochemical, and metabolic influence of glycemic variability on tumor behavior. A set of in vivo functional assays including orthotopic implantation and portal and tail vein injection were used. Results were further confirmed on tissues from PDAC patients. Results: Glycemic variability has no significant effect on PDAC cell proliferation. Hypoglycemia is associated with local invasion and angiogenesis, whereas hyperglycemia promotes metastatic colonization. Increased metastatic colonization under hyperglycemia is due to increased expression of runt related transcription factor 3 (Runx3), which further activates expression of collagen, type VI, alpha 1 (Col6a1), forming a glycemic pro-metastatic pathway. Through epigenetic machinery, retinoic acid receptor beta (Rarb) expression fluctuates according to glycemic variability, acting as a critical sensor relaying the glycemic signal to Runx3/Col6a1. Moreover, the signal axis of Rarb/Runx3/Col6a1 is pharmaceutically accessible to a widely used antidiabetic substance, metformin, and Rar modulator. Finally, PDAC tissues from patients with diabetes show an increased expression of COL6A1. Conclusions: Glycemic variability promotes both local invasion and metastatic colonization of PDAC. A pro-metastatic signal axis Rarb/Runx3/Col6a1 whose activity is controlled by glycemic variability is identified. The therapeutic relevance of this pathway needs to be explored in PDAC patients, especially in those with diabetes. Keywords: Pancreatic Cancer, Glucose Metabolism, Metastasis, Retinoic Acid